2021
DOI: 10.3390/polym13244336
|View full text |Cite
|
Sign up to set email alerts
|

Review of Recent Developments of Glass Transition in PVC Nanocomposites

Abstract: This review addresses the impact of different nanoadditives on the glass transition temperature (Tg) of polyvinyl chloride (PVC), which is a widely used industrial polymer. The relatively high Tg limits its temperature–dependent applications. The objective of the review is to present the state–of–the–art knowledge on the influence of nanofillers of various origins and dimensions on the Tg of the PVC. The Tg variations induced by added nanofillers can be probed mostly by such experimental techniques as thermome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 118 publications
3
21
1
Order By: Relevance
“…The foam used for testing has a minimum weight of 3 mg. 7 shows that the more Mg or Zn is added, the higher the glass transition temperature (Tg). The increases in the concentration of the additives reduce the molecular mobility of the matrix, which results in the shift of the foams Tg to a higher temperature [24]. The DSC result also supports the SEM test results shown in Fig.…”
Section: Dsc (Differential Scanning Calorimetry) Analysissupporting
confidence: 84%
“…The foam used for testing has a minimum weight of 3 mg. 7 shows that the more Mg or Zn is added, the higher the glass transition temperature (Tg). The increases in the concentration of the additives reduce the molecular mobility of the matrix, which results in the shift of the foams Tg to a higher temperature [24]. The DSC result also supports the SEM test results shown in Fig.…”
Section: Dsc (Differential Scanning Calorimetry) Analysissupporting
confidence: 84%
“…Results showed that Bi 2 O 3 powder ChemistrySelect had inert character and there were no change between these temperature ranges. [49] TGA curves of PVC-0 and PVC-3 were nearly similar each other and had three stages of degradation; first stages at 237 °C and 243 °C, respectively. [50,51] It is reported that mass loss of neat PVC nanofibers are less than PVC granules and this means that nanofiber manufacturing limits mass loss caused by thermal applications.…”
Section: Surface Morphology Of Bi 2 O 3 -Loaded and Neat Pvc Electros...mentioning
confidence: 69%
“…The total enthalpy variation of PVC‐0 was detected as 27.32 J/g which was higher than that of PVC‐10 nanofibers (21.21 J/g) TGA analysis was performed with temperature raise of 10 °C between 30 °C and 800 °C. Results showed that Bi 2 O 3 powder had inert character and there were no change between these temperature ranges [49] . TGA curves of PVC‐0 and PVC‐3 were nearly similar each other and had three stages of degradation; first stages at 237 °C and 243 °C, respectively [50,51] .…”
Section: Resultsmentioning
confidence: 89%
“…[114][115][116] Moreover, adding foreign particles (such as plasticizers, surfactants, or nanoparticles) also helps in tuning the glass transition temperature essential for developing versatile shape memory polymers. [117][118][119] Wang et al showed a blend of SBS tri-block copolymer and an amorphous polymer poly(dl-lactic acid) (dl-PLA) that recovered to its permanent shape when heated to 80 C. 111 Figure 15 shows the variation of the shape memory properties when varied the PLA content. When the PLA content has increased, the recovery (%) drops from 93.7% to 88.5%, while the fixity(%) enhances from 38.9% to 94.3%.…”
Section: Sbs-based One-way Shape Memory Polymersmentioning
confidence: 99%